Water quality in the Upper Citarum River Basin: towards a better understanding of a heavily polluted catchment - van Ginkel, Kees (Student Undergraduate Research E-journal!, 2016)
The Upper Citarum River Basin is a heavily polluted catchment on West Java, Indonesia. Policy makers and scientist show increasing interest for the issue, but there is no recent scientific study that gives an overview of the current state of the river basin. In this paper, the six drivers of the water quality problem are described by system analysis, tracing them back to weak social and governmental institutions. Stakeholder analysis reveals a strong mismatch between responsibilities, authorities and resources among monitoring stakeholders. Data analysis shows that the industry is the largest polluter of the basin, followed by pollutants from domestic origin.